The Effects of Self Construal on Domain-Specific Risk Taking Behaviour - Anant, Nandini (2019)
Previous research has shown that individuals from Chinese cultures take more financial risks than individuals from American cultures, a difference that is not observed in other types of risk taking behaviours and attributed to the collectivistic nature of Chinese culture acting as a mitigative cushion against negative outcomes – termed the cushion hypothesis (Weber &Hsee, 1998). This PhD was an investigation into how self construal (the way that individuals define themselves) – as another way of conceptualising cross-cultural differences – affects risk taking behaviours across domains, including financial risks. Findings indicated that, contrary to previous studies, regardless of culture, an individual’s self construal was a key determinant of financial risk taking and the cushion hypothesis. In addition, perception of support, perceptions of benefits and risks, and anticipated affect were found to be important proximal determinants of financial risk taking behaviour and an explanation for the cushion hypothesis. Data also indicated the existence of a shielding effect of self construal – we find that an individual’s self construal could act as a buffer against risk taking behaviours in the health/safety and recreational domains due to anticipated affect relating to actions considered and feelings of accountability towards others. The findings from my PhD have a number of practical implications for risk taking behaviours. Firstly, my findings could be incorporated into communications and messages around reducing risk taking behaviour (including gambling) by framing them in such a way so as to highlight self construal and feelings of accountability towards others. Secondly, they could be used when designing interventions to identify sections of society who might be at higher risk of engaging in risk taking behaviours.